Factors Associated with The Incidence of Chronic Energy Deficiency (CED) n Third Trimester Pregnant Women In The Working Area of The Lubuk Begalung Health Center, Padang City - Agustianov, Indah; Lestari, Yuniar; Lisa, Ulfa Farrah; Rita, Rauza Sukma; Hudzaifah, Hindun Mila (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: The World Health Organization (WHO) reports a global prevalence of Chronic Energy Deficiency (CED) in pregnancy ranging from 35-75%. In Padang City’s Lubuk Begalung Region, the 2022 health profile indicated a 12.9% incidence of CED among 1,268 pregnant women. Several factors influence CED incidence, including age, economic status, education, pregnancy spacing, parity, employment, and antenatal care (ANC) visits. Purpose: To identify factors associated with CED among third-trimester pregnant women in the Lubuk Begalung Health Center Working Area. Methods: This cross-sectional analytical study involved 57 respondents selected through simple random sampling. Inclusion criteria were third-trimester pregnant women aged 24-40 weeks who could communicate effectively, excluding those who could not be contacted after three attempts. Data collection involved interviews using a structured questionnaire, and analyses were performed using chi-square and logistic regression with a 95% confidence interval. Results: CED was observed in 21 respondents (36.8%). Key factors included age <20 or >35 years (59.3%), low economic status (55.0%), low education level (53.8%), unemployment (51.5%), and ?3 ANC visits (56.5%). Age was the dominant factor (p = 0.005, b = 6.623). Conclusion: Age, education, occupation, and ANC visits were significantly associated with CED, while economic status, pregnancy spacing, and parity were not. Future studies should explore additional factors influencing CED.